Alkaline Phosphatase: The Poor Man’s iPTH - An Affordable Approach to Bone Health Assessment - Sourabh Sharma; Himanshu Verma; Sanjay Kalra (Journal of the Pakistan Medical Association, 2024)
This review delves into relatively less discussed role of alkaline phosphatase (ALP) as an accessible alternative to intact parathyroid hormone (iPTH) in the context of bone health assessment, particularly focussing on its potential boon for underprivileged individuals with chronic kidney disease (CKD) in South Asia. The financial constraints faced by this demographic often hinder regular monitoring of iPTH levels. ALP emerges as a promising surrogate, offering a cost-effective and practical solution for bone health evaluation in resource-constrained settings. Keywords: PTH, Intact Parathormone, Alkaline Phosphatase, ALP, Chronic Kidney Disease, Bone Health